PENGATURAN IDEAL ORGANISASI SAYAP PARTAI POLITIK - Elviandri, Elviandri; Ardiansyah, Ardiansyah; Suswadi, Suswadi; Riza, Wahyu Friyonanda (LPPM, Universitas Muhammadiyah Riau, 2024)
Party Wing Organizations play a strategic role in supporting political parties to strengthen their reach to various levels of society, especially in the process of gathering support, advocacy and interest mediation. However, the legal arrangements that bind these organizations are still being debated, especially in terms of whether they should be subject to the same regulations as general social organizations or obtain special status under the legal umbrella of political parties. This research uses normative juridical methods, with statutory, historical and conceptual approaches. Arrangements regarding Party Wing Organizations still have challenges that require further attention. One of the ideal concepts proposed is that the position and role of party wing organizations should be explained in more detail in the revision of the Political Party Law. This is important to provide clarity regarding the rights and obligations of wing organizations as well as their operational boundaries so that they do not overlap with the role of their parent political parties and play an active role in mainstreaming gender equality and social inclusion in politics. Party wing organizations are legal entities, so as legal subjects they can be sued in the criminal, civil and administrative realms. This recognition is important to clarify the legal status of party wing organizations and prevent a legal vacuum if a dispute or legal violation occurs involving the organization.